Aktivitas Ekstrak Etanol Umbi Bawang Tiwai (Eleutherine americana (Aubl.) Merr) terhadap Kelarutan Kalsium Batu Ginjal secara In Vitro - Triani Yastuti Kuling; Jaka Fadraersada; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Kidney stones are a disease that occurs due to the deposition of compounds that are difficult to dissolve because the body lacks fluids. Bawang Tiwai (Eleutherine americana (Aubl.) Merr) is an endemic Dayak plant in Kalimantan which has been traditionally used as traditional medicine dayak’s people. One of the active components is flavanoid which can dissolve kidney stones. This study aims to determine the concentration activity of the bawang tiwai roots extract to dissolve kidney stone calcium. The extract was made by maceration method using ethanol 96%. The extraction activity testing used 5 treatments namely 1 ppm, 2 ppm, 3 ppm, negative control (distilled water) and positive control (elixir stone). Kidney stones were then added as much as 10 mg to each treatment. After the addition of kidney stones in each treatment incubation for 3 hours at 37 ?. Calcium solubility activity was seen by using a UV-Visible spectrophotometer by measuring the absorbance value of each test concentration. The results showed that the 3 ppm concentration was the optimal concentration in dissolving kidney stone calcium in vitro.